The African Book Publishing Record (De Gruyter Saur, 1975)
The African Book Publishing Record (ABPR) is the only bibliographical tool which offers systematic and comprehensive coverage of new African publications in a single source, providing full bibliographic and acquisitions data. In addition to its bibliographic coverage, ABPR also includes an extensive book review section, reviews of new journals, and features a variety of reports about African book trade activities and developments.